Late stage at diagnosis of colorectal cancer & its associated factors among patients in Kedah from 2007 to 2011 : a review from Kedah cancer registry - Marzuki, Muhamad Fadhil Mohamad (2016)
Background: Colorectal cancer is among the highest number of cancer reported in Kedah. It is the second most common cancer in Kedah in year 2007 to 2011 after breast cancer. Clinical observation also suggested a high proportion of colorectal cancer cases in Kedah presented at late stage of diagnosis leading to poor outcome and reduce chances of survival. Objectives: This study was conducted with the aim to describe the sociodemographic and clinical characteristics of the colorectal cancer patients and the percentage of late stage at diagnosis. It was also conducted to determine the associated factors of the late stage at diagnosis of colorectal cancer among patients in Kedah population from year 2007 to 2011. Methodology: A cross sectional study was conducted in January 2016 using secondary data obtained from the Kedah Cancer Registry. Four hundred twenty five data was randomly selected for analysis. Result: The mean(SD) age was 60.3(13.40) years old with majority were male 250 cases (58.8%), Malay race 233 cases (54.8%), urban patient 283 cases (66.6%), having colon cancer 282 cases (66.4%) and almost all of them are adenocarcinoma 397 cases (93.4%). One hundred thirty one of them (30.8%) are in stage II followed by stage III 128 cases (30.1%), stage IV 88 cases (20.7%) and stage I 78 cases (18.4%). More than half were in late stage 216 cases (50.8%). Logistic regression analysis found that only cancer morphology are associated with late stage at diagnosis of colorectal cancer in Background: Colorectal cancer is among the highest number of cancer reported in Kedah. It is the second most common cancer in Kedah in year 2007 to 2011 after breast cancer. Clinical observation also suggested a high proportion of colorectal cancer cases in Kedah presented at late stage of diagnosis leading to poor outcome and reduce chances of survival. Objectives: This study was conducted with the aim to describe the sociodemographic and clinical characteristics of the colorectal cancer patients and the percentage of late stage at diagnosis. It was also conducted to determine the associated factors of the late stage at diagnosis of colorectal cancer among patients in Kedah population from year 2007 to 2011. Methodology: A cross sectional study was conducted in January 2016 using secondary data obtained from the Kedah Cancer Registry. Four hundred twenty five data was randomly selected for analysis. Result: The mean(SD) age was 60.3(13.40) years old with majority were male 250 cases (58.8%), Malay race 233 cases (54.8%), urban patient 283 cases (66.6%), having colon cancer 282 cases (66.4%) and almost all of them are adenocarcinoma 397 cases (93.4%). One hundred thirty one of them (30.8%) are in stage II followed by stage III 128 cases (30.1%), stage IV 88 cases (20.7%) and stage I 78 cases (18.4%). More than half were in late stage 216 cases (50.8%). Logistic regression analysis found that only cancer morphology are associated with late stage at diagnosis of colorectal cancer in which other type of colorectal cancer such as mucinous adenocarcinoma, signet ring cell carcinoma, and squamous cell carcinoma were nearly 3 times higher risk of having late stage at diagnosis of colorectal cancer (Adj.OR 2.71, 95% CI: 1.17, 6.25; p = 0.020) as compared to adenocarcinoma. Conclusion: There are high proportion of colorectal cancer in Kedah presented with late stage at diagnosis, mainly if the morphology is other than adenocarcinoma.